Screening for the antimicrobial activity of Salvadora persica extracts against Enterococcus faecalis and Candida albicans - Hanan Balto; Tawfeq Al-Howiriny; Ali Al-Somily; Yunus M Siddiqui; Zeyad Al-Sowygh; Hassan Halawany; Zahid Shakoor; Solaiman Al-Hadlaq (International Journal of Phytomedicine, 2013)
Antimicrobial resistance of Enterococcus faecalis (E. faecalis) and Candida albicans (C.albicans), frequently implicated in dental infections, remains a challenge. Using a variety of solvents this study was performed to screen the antimicrobial activity of Salvadora persica (S. persica) extracts against these two organisms. Seven extracts of S. Persica were prepared using hexane, chloroform, ethyl acetate, methanol-soluble, methanol-insoluble, ethanol, and water. Antimicrobial activities against E. faecalis and C.albicans were assessed by colony forming unit (CFU) counts after 1, 3, 6 and 24 hours of exposure using doubling dilutions of the extracts ranging between 125 µg to 1mg/ml. Among the extracts of S. persica tested, hexane extract induced a steady and progressive reduction in CFUs of both the E. faecalis (p<0.001) and C. albicans (p<0.01) at all concentrations beginning after 3 hours until 24 hours. Progressive inhibition of E. faecalis CFUs was also observed for ethanol beginning at 3 hours until 24 hours (p <0.001) and chloroform only at 24 hours (p<0.001) at all concentrations. Ethyl acetate extract of S. persica was effective against C. albicans at 250µg/mg after 6 hours (p<0.02) and 24 hours (p <0.002). No significant changes were observed in any of the other tested extracts of S. persica. Hexane extract of S. persica was found to exhibit maximum antimicrobial activity against E. faecalis and C.albicans. Further studies are recommended for evaluation of this extract as an effective anti-microbial agent.